Everyday Advocates. (August 2015) - Walker, Deborah Kirk; Barton-Burke, Margaret; Saria, Marlon Garzo; Gosselin, Tracy; Ireland, Anne; Norton, Victoria; Newton, Susie
<x xml:space="preserve">Abstract</x> Nurses stand up for patients, colleagues, the profession, and themselves.